Performance Analysis for Uniform and Binomial Distribution on Contention Window using DSRC and Wi-Fi Direct Standard - Nurain Izzati Shuhaimi; Heriansyah Heriansyah; Tutun Juhana; Adit Kurniawan (International Journal of Electrical and Computer Engineering (IJECE), 2015)
In this paper, we present a mathematical analysis on the performance and behavior of uniformly distributed and non-uniformly distributed backoff timer based on binomial algorithm by using two standards which is the conventional DSRC and the latest Wi-Fi Direct. DSRC is a well-known technology being considered as the most promising wireless standard in VANET. On the other hand, as the latest wireless networking standard, the potential of Wi-Fi Direct technology should be concerned. We evaluates these standards using uniform and binomial distribution for contention window under mathematical modelling in order to analyze the average throughput and collision probability performance. The results show that binomial distribution in Wi-Fi Direct standard is 7.05% and 97.13% better than uniform distribution, in terms of average throughput and collision probability, respectively. Thus we can defer that Wi-Fi Direct is feasible to be used as an alternative standard since it has been considered as potential competitor of DSRC in VANET.